Effects of local application of the ankaferd blood stopper on osseointegration in three different surface titanium implants - Ozcan, Erhan Cahit; Gul, Mehmet; Dundar, Serkan; Bozoglan, Alihan; Karasu, Necmettin; Bal, Ali; Bingul, Muhammet Bahattin (Elsevier B.V., 2021)
Objective: Researchs of the effects of ankaferd blood stopper (ABS) on bone healing metabolism have revealed that it affects bone regeneration positively. The exact mechanism by which this positive effect on bone tissue metabolism is not known. The aim of this study is to biomechanic and biochemical analysis of the effects of the local ABS application on osseointegration of 3 different surfaced titanium implants. Material & Methods: Spraque dawley rats were divided machined surfaced (MS) (n ?= ?10), sandblasted and large acid grid (SLA) (n ?= ?10) and resorbable blast material (RBM) (n ?= ?10) surfaced implants. ABS applied locally during the surgical application of the titanium implant before insertion in bone sockets. After 4 weeks experimental period the rats sacrificed and implants with surrounding bone tissues were removed to reverse torque analysis (Newton), blood samples collected to biochemical analysis (ALP, calcium, P) Results: Biomechanic bone implant contact ratio detected higher in SLA surfaced implants compared with the RBM and controls (P ?< ?0,05). Phosphor levels detected lower in RBM implant group compared with the controls and SLA (P ?< ?0,05). Additionally; phosphor levels detected highly in controls compared with the RBM implants. Conclusion: According the biomechanical parameters ABS may be more effective in SLA and RBM surfaced implants when locally applied. © 2021 Craniofacial Research Foundation
Keywords: Ankaferd blood stopper; Biomechanic; Bone implant contact; Implant surfaces; Osseintegration